Prevalence of Dyslipidemia in Geriatric rural Population Residing in a Hilly District of Uttarakhand State, India - Khandelwal, Ritika; Gupta, Aakriti; Kapil, Umesh (Indian Journal of Community Health, 2018)
Background: Dyslipidemia is a major contributing determinant in the development of ischemic heart diseases, stroke, and other vascular diseases. It increases the risk of mortality amongst the geriatric population. Objective: To assess the prevalence of dyslipidemia in geriatric rural population residing in a hilly district of Uttarakhand state, India. Methodology: A community based cross-sectional study was conducted during 2015-2016 in District Nainital, Uttarakhand. A list of all villages with their population in the district was developed. From this list, thirty villages were identified using population proportionate to size sampling method. From each village 30 geriatric subjects were selected. A total of 1003 geriatric subjects aged 60 years and above were included in the study. The data was collected on socio demographic profile and lipid profile from all the enrolled subjects. The prevalence of dyslipidemia was assessed using National Cholesterol Education Programme (NCEP) criteria. Result: The overall prevalence of dyslipidemia was 50.6%. A total of 26.3% participants had hypercholesterolemia, 34.2% had hypertriglyceridemia and 23.5% had high LDL levels. The prevalence of dyslipidemia was higher in women compared to men. Conclusion: High prevalence of dyslipidemia was found amongst geriatric rural population.